Current evidence for nonpharmacological interventions and criteria for surgical management of persistent acromioclavicular joint osteoarthritis: A systematic review. (December 2019) - Farrell, Gerard; Watson, Lyn; Devan, Hemakumar
Background: The primary aim of this systematic review was to investigate the individual/combined effectiveness of nonpharmacological interventions in individuals with persistent acromioclavicular joint osteoarthritis. The secondary aims were to investigate the comparative effectiveness of nonpharmacological versus surgical interventions, and to identify the criteria used for defining failure of conservative interventions in individuals who require surgery for persistent acromioclavicular joint osteoarthritis. Method: Major electronic databases were searched from inception until October 2018. Studies involving adults aged 16 years and older, diagnosed clinically and radiologically with isolated acromioclavicular joint osteoarthritis for at least three months or more were included. Studies must explicitly state the type and duration of conservative interventions. Methodological risk of bias was assessed using the Modified Downs and Black checklist. Results: Ten surgical intervention studies were included for final synthesis. No studies investigated the effectiveness of nonpharmacological interventions or compared them with surgical interventions. Common nonpharmacological interventions trialed from the 10 included studies were activity modification (n = 8) and physiotherapy (n = 4). Four to six months was the most often reported timeframe defining failure of conservative management (range 3–12 months). Conclusions: Currently, there is no evidence to guide clinicians about the individual or combined effectiveness of nonpharmacological interventions for individuals with persistent acromioclavicular joint osteoarthritis.